PENGGUNAAN RELASI KOHESI GRAMATIKAL DALAM CERPEN PERADILAN RAKYAT KARYA PUTU WIJAYA - Yuli Yanti; Mulyanto Widodo; Ni Nyoman Wetty Suliani (FKIP Universitas Lampung, 2013)
The problem of this research is using relasi cohesi grammatical in short story Peradilan Rakyat by Putu Wijaya and the implication on learning Indonesian language at SMA. The objective of the research was to know the implication of Indonesian language using relasi cohesi grammatical in short story Peradilan Rakyat by Putu Wijaya at SMA. The menthod of collecting data was descriptive menthod which explain situation the object research was story Peradila Rakyat by Putu Wijaya. In collecting the data, the researcher used reading and writing technique. Based on result of research short story by Peradilan Rakyat by Putu Wijaya, the total sentence that using relasi cohesi grammatical was 193, after than analysed based on using clarification cohesi grammatical is that found 503. Using relasi cohesi grammatical is that found including reference, subsitution, ellipsis, and conjunction. Relasi cohesi grammatical can be material adding on learning in standard competence writing, using relasi cohesi grammatical can be applicated as alternative materi on learning of writing and paragraph.Key words : grammatical, reference, subsitution, ellipsis, conjunction